Replicable stories for the expansion of water reuse in MENA - International Water Management Institute (International Water Management Institute, 2022)
The potential for resource recovery from municipal wastewater in MENA is still untapped. The number of projects for direct water reuse has doubled every decade since 1990 and now the region has more than 400. Despite the progress, only around 10% of the generated municipal wastewater in the region is (treated and) reused directly. Nevertheless, there are bright examples that can inspire the region and a number of recommendations that can accelerate action for more and safer water reuse in the region. This video showcases some of these stories and recommendations.